CXC Chemokine Receptor 2 Accelerates Tubular Cell Senescence and Renal Fibrosis via β-Catenin-Induced Mitochondrial Dysfunction - Meng, Ping; Huang, Jiewu; Ling, Xian; Zhou, Shan; Wei, Jingyan; Zhu, Mingsheng; Miao, Jinhua; Shen, Weiwei; Li, Jiemei; Ye, Huiyun; Niu, Hongxin; Zhang, Yunfang; et al. (Frontiers in Cell and Developmental Biology, 2022)
Renal fibrosis is a common feature of various chronic kidney diseases (CKD). However, its underlying mechanism has not been totally clarified. C-X-C motif chemokine receptor (CXCR) family plays a role in renal fibrosis, however, detailed mechanisms have not been elucidated. Here, we report that CXCR2 has a potential role in tubular cell senescence and renal fibrosis, and is associated with β-catenin-activated mitochondrial dysfunction. CXCR2 is one of most increased members among CXCR family in unilateral ureteral obstruction (UUO) mice. CXCR2 was expressed primarily in tubules and co-localized with p16INK4A, a cellular senescence marker, and β-catenin. Administration of SB225002, a selective CXCR2 antagonist, significantly inhibited the activation of β-catenin signaling, restored mitochondrial function, protected against tubular cell senescence and renal fibrosis in unilateral ureteral obstruction (UUO) mice. In unilateral ischemia-reperfusion injury (UIRI) mice, treatment with interlukin-8 (IL-8), the ligand of CXCR2, further aggravated β-catenin activation, mitochondrial dysfunction, tubular cell senescence and renal fibrosis, whereas knockdown of p16INK4A inhibited IL-8-induced these effects. In vitro, SB225002 inhibited mitochondrial dysfunction and tubular cell senescence. Furthermore, ICG-001, a β-catenin signaling blocker, significantly retarded CXCR2-induced cellular senescence and fibrotic changes. These results suggest that CXCR2 promotes tubular cell senescence and renal fibrosis through inducing β-catenin-activated mitochondrial dysfunction.